2016
DOI: 10.4314/njp.v43i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of mother to child transmission of hepatitis B virus infection in Nigeria: A call to action

Abstract: Abstract:Background: Sub-Sahara Africa including Nigeria has the second largest global burden of chronic carriers of hepatitis B virus (HBV) infection after Asia. Mother-to-child transmission (MTCT) of HBV is the most commonroute of transmission in high endemic areas .MTCT of hepatitis B virus infection continues to occur despite the interventions of hepatitis B vaccinations and immunoglobulins in settings where it is practiced. Infants most at risk are those whose mothers have high HBV DNA viral loads and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…There are also Research Institutes and training institutions supporting learning and dissemination of research products, yet research is still underfunded in most of these institutions (FMoH, 2016a). Research on advances in HBV is currently carried out by some societies such as the Society for Gastroenterology and Hepatology in Nigeria (SOGHIN) and the Nigerian Society for Paediatric Gastroenterology Hepatology and Nutrition (NISPGHAN) (Eke et al, 2016). A Hepatitis cancer registry is maintained by the National Cancer Control Programme, an arm of the FMoH, yet, routine HBV infection surveillance are not conducted in Nigeria (Howell et al, 2014).…”
Section: Health Information and Researchmentioning
confidence: 99%
“…There are also Research Institutes and training institutions supporting learning and dissemination of research products, yet research is still underfunded in most of these institutions (FMoH, 2016a). Research on advances in HBV is currently carried out by some societies such as the Society for Gastroenterology and Hepatology in Nigeria (SOGHIN) and the Nigerian Society for Paediatric Gastroenterology Hepatology and Nutrition (NISPGHAN) (Eke et al, 2016). A Hepatitis cancer registry is maintained by the National Cancer Control Programme, an arm of the FMoH, yet, routine HBV infection surveillance are not conducted in Nigeria (Howell et al, 2014).…”
Section: Health Information and Researchmentioning
confidence: 99%
“…8 In Nigeria, MTCT rates of HBV vary from 8.3% to 12.8%. 6 There are limited reports on MTCT rates of HCV in Nigeria as it is often not routinely screened. However, the burden of HIV/HCV MTCT may also be significant given the reported rate of 5.2% of pediatric HIV/HCV co-infections.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] In a Nigerian pediatric HIV program, 7.7% and 5.2% of the HIV-infected children were co-infected with HBV and HCV, respectively. 6 Fortunately, the MTCT of these infections of public health importance can be prevented or eliminated through simple interventions involved in prevention of mother-to-child transmission (PMTCT) programs. 7 However, these programs are poorly coordinated.…”
Section: Introductionmentioning
confidence: 99%
“…Although a higher prevalence of HBV infection is reported among surgeons (25.7%), voluntary blood donors (23.4%), and infants (25.7%), Hepatitis B surface antigenemia (HBsAg) studies of pregnant women in Nigeria have revealed HBV prevalence of between 2% and 15.2%. [ 11 12 ] In Zaria and Ilorin both in Northern-central Nigeria, studies showed HBV prevalence in pregnancy to be 8.2% and 5.7%, respectively. [ 13 14 ] Previous studies on risk factors for HBV infection in pregnancy have shown that high parity, history of blood transfusion, HBV infection in family members, tattooing, and previous surgeries are known risk factors for HBV infection in pregnancy.…”
Section: Introductionmentioning
confidence: 99%